The Reputation of the Indonesian National Police (Polri) (Narrative Network Analysis on Instagram @korlantaspolri.ntmc) - Fattiha Ahsan, Titania; Yuniar, Ririt (Sekolah Tinggi Ilmu Kepolisian, 2025)
Social media interactions play a significant role in shaping public opinion through narratives circulating within digital networks, which influence the reputation of the Indonesian National Police (Polri), both positively and negatively. This phenomenon became particularly visible following the implementation of Operation Ketupat 2025, which attracted public attention due to traffic congestion during the homecoming period and triggered widespread reactions from netizens on social media. This study analyzes the narrative network of Polri’s reputation on the Instagram account @korlantas.ntmc, aiming to identify key actors who occupy central positions in creating, shaping, and disseminating narratives. The research is grounded in the concepts of narrative analysis within social network analysis (SNA) and Instagram as a Social Network Site (SNS). A mixed-method approach with a qualitative descriptive emphasis was employed. Data were collected by identifying nodes and links from Instagram comments using IGcomment and analyzed with Gephi 0.10.1 to visualize the narrative network and assess reputation dynamics. The findings reveal two key actors based on degree, betweenness, and closeness centrality measurements in the post titled “Member of the Indonesian House of Representatives Habiburokhman: This is the Smoothest Homecoming in History.” These findings provide insights for future research on narrative networks and digital reputation management. To reduce negative public responses, Polri should consistently reflect the values of the nation’s four basic consensuses, encouraging more constructive and responsible discourse on social media.